Voices from the classroom: pre-service teachers’ interactions with supervising teachers - Moosa, Moeniera; Rembach, Lauren (University of the Free State, 2018)
Teaching practice is an important requirement to acquire a teaching qualification from South African universities. During teaching practice, it is customary for supervising teachers to guide and evaluate the students’ performance. However, very little is known about how the interaction with supervising teachers influences the students’ views about the teaching profession. Forty final-year Bachelor of Education students at the University of the Witwatersrand gave their consent to participate in a qualitative study using open-ended questionnaires. This research aimed to explore pre-service teachers’ voices, using Denise Batchelor’s (2008; 2006) research pertaining to conceptualisations of voice, namely, practical, epistemological and ontological, which were used to analyse the data. The findings suggested that pre-service teachers’ pedagogical choices were linked to the supervising teachers’ guidance. Many of the supervising teachers framed teaching as a profession that foregrounded administrative tasks and classroom management. Some of the supervising teachers’ negative perceptions of the profession caused pre-service teachers to question their choice to become teachers. Another issue was that pre-service teachers wish to feel welcomed and supported at schools, but most experienced a lack of mentorship from their supervising teachers. We recommend that supervising teachers attend workshops and courses on how to mentor pre service teachers.
Keywords: Teaching practice; Pre-service teachers; Voices; Professional practice; Mentorship; Supervising teachers